2014
DOI: 10.1111/mec.12650
|View full text |Cite
|
Sign up to set email alerts
|

Landscape effects on gene flow for a climate‐sensitive montane species, theAmerican pika

Abstract: Climate change is arguably the greatest challenge to conservation of our time. Most vulnerability assessments rely on past and current species distributions to predict future persistence but ignore species' abilities to disperse through landscapes, which may be particularly important in fragmented habitats and crucial for long-term persistence in changing environments. Landscape genetic approaches explore the interactions between landscape features and gene flow and can clarify how organisms move among suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
163
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(173 citation statements)
references
References 69 publications
5
163
0
1
Order By: Relevance
“…It is therefore difficult to anticipate biases in PCA-based conclusions. Although PCA has not been widely applied in landscape genetic studies, Shirk et al (2012) found consistent causal modeling outcomes when using PCA, proportion of shared alleles and Rousset's a (Rousset 2000), and Castillo et al (2014) found genetic distance based on Bray-Curtis percent dissimilarity (Legendre and Legendre 1998) was similar to PCA genetic distance. We detected significant landscape variables within all three regions despite relatively low sample size, supporting the utility of PCA in landscape genetic studies of continuously distributed species.…”
Section: Study Limitationsmentioning
confidence: 76%
See 2 more Smart Citations
“…It is therefore difficult to anticipate biases in PCA-based conclusions. Although PCA has not been widely applied in landscape genetic studies, Shirk et al (2012) found consistent causal modeling outcomes when using PCA, proportion of shared alleles and Rousset's a (Rousset 2000), and Castillo et al (2014) found genetic distance based on Bray-Curtis percent dissimilarity (Legendre and Legendre 1998) was similar to PCA genetic distance. We detected significant landscape variables within all three regions despite relatively low sample size, supporting the utility of PCA in landscape genetic studies of continuously distributed species.…”
Section: Study Limitationsmentioning
confidence: 76%
“…The use of Mantel testing in landscape genetics is controversial (Raufaste and Rousset 2001;Guillot and Rousset 2013;Graves et al 2013), but multiple analyses defend the use of this method within a causal modeling framework (Cushman and Landguth 2010;Shirk et al 2010;Cushman et al 2013b;Castillo et al 2014). Legendre and Fortin (2010) The effect of genetic distance metric choice on causal modeling outcomes has not been evaluated within the field of landscape genetics.…”
Section: Study Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…More recent studies indicate a wide range of dispersal distances including < 20 km (hafner 1993), ≥ 2 km (Zgurski and hik 2012), 2-10 km (Peacock 1997), and 3 km (Merideth 2002). topographic complexity, water barriers, and west-facing slopes were the major factors found to restrict pika dispersal in oregon (Castillo et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…When landscapes are complex, organisms perceive contrasts in habitat quality or risk among alternative pathways that may modify movement behavior and dispersal rates . Increased diversity and contrast of land-cover types, may disrupt isolation by distance relationships (Bender & Fahrig 2005, Heidinger et al 2013 making it more informative to analyze effective distances that account for species responses to landscape features , Castillo et al 2014, Soare et al 2014.). Local scale experiments can be used to estimate effective distances by providing information on species-specific responses to landscape features , such as gap crossing behavior (Smith et al 2013) and habitat-specific survival .…”
Section: Introductionmentioning
confidence: 99%